Phenolic and anthocyanin content characterization related to genetic diversity analysis of Solanum tuberosum subsp. tuberosum Chilotanum Group in southern Chile - Behn, Anita; Lizana, Carolina; Zapata, Felipe; Gonzalez, Alvaro; Reyes-Díaz, Marjorie; Fuentes, Derie (Frontiers in Plant Science, 2023)
The potato (Solanum tuberosum L) is one of the four most important crops worldwide in production and consumption. It originated from South America along the Andes, where six hotspots of diversity known as subcenters of origin are described from Venezuela to Chiloe Island in Chile, and where the greatest diversity of potatoes in the world is found. Today, the use of ancestral genetic resources has gained significant relevance, recovering and producing foods with a greater nutrient content and beneficial to human health. Therefore, native potatoes possess a set of characteristics with great potential for use in potato breeding guided primarily to produce better feed, especially potatoes of the Chilotanum Group that are easily crossed with conventional varieties. The primary objective of this study was to evaluate 290 accessions of S. tuberosum subsp tuberosum belonging to the Chilotanum Group using a set of molecular markers and correlate them to its phenotypic traits for future use in breeding programs. For this purpose, 290 accessions were analysed through 22 specific microsatellites described previously, correlating them with flesh and skin colour, total phenolic content, and anthocyanin content. A division into groups considering all the 290 accessions resulted in two clusters using STRUCTURE analysis and seven different genetic clusters using UPGMA., The latter exhibited common phenotypic characteristics as well as anthocyanin content, strongly supporting a correlation between phenotypic traits and the genetic fingerprint. These results will enable breeders to focus on the development of potatoes with high polyphenol and anthocyanin content.